Design and in-situ biomimetic fabrication of a high-density strain sensor array for parachute canopy fabric - Hui Li; Jiangang He; Chunzu Liang; Fengjiao Bin; Xu Li; Xianda Wang; Zihao Wang; Xiangxiao Bu; Dengbao Xiao; He Jia; Wei Rong (iScience)
Summary: In-situ monitoring of non-uniform strains in spacecraft parachute canopies is essential to ensure safe landings. Traditional wearable strain sensors struggle to meet high-resolution measurement requirements due to their low density. In-situ inkjet printing offers a promising solution for fabricating high-density strain sensor arrays directly on the fabric surface. However, capillary effects in the canopy fabric cause droplet leakage, hindering stable printing. To address this, we drew inspiration from nature, using modified silane to mimic the wax layer of coconut husk for modifying the canopy fabric, which enabled the in-situ fabrication of a strain sensor array via inkjet printing. This modification overcame capillary effects and balanced the fabric’s wettability, essential for stable printing. Furthermore, a layered printing strategy was designed to increase sensor density to 4 units·cm−2, facilitating high-resolution measurement of non-uniform strains in the canopy. This study offers a feasible approach for developing sensors for large-scale parachute strain measurements.